2018
DOI: 10.1111/cote.12376
|View full text |Cite
|
Sign up to set email alerts
|

Fungal colorants in applications – focus on Cortinarius species

Abstract: Secondary metabolites in fungi offer an interesting source of bio-based compounds that could be used as colorants in many applications. From a historical point of view, fungal natural dyes have been used more rarely than plant-based dyes. This paper investigates the potential of fungal colorants, using Cortinarius species as examples. In our research, fruiting bodies of the fungi Cortinarius sanguineus and Cortinarius semisanguineus were used as sources of anthraquinone dyestuffs. From 10 kg of fresh fruiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…In a previous study, anthraquinone dyestuff (60g anthraquinone powder from 10 kg fresh mushroom) was obtained in fruiting bodies of Cortinarius sanguineus and C. semisanguineus collected from Kuopio and Tuusula region of Finland, respectively [53] and natural and synthetic fibres were dyed with pure emodin and dermocybin found as major compounds in both Cortinarius species, as well as tap water extract. It was found that natural anthraquinones which produced light and dark colors such as yellow, orange and brown, could be suitable in dyeing and printing different textile materials.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, anthraquinone dyestuff (60g anthraquinone powder from 10 kg fresh mushroom) was obtained in fruiting bodies of Cortinarius sanguineus and C. semisanguineus collected from Kuopio and Tuusula region of Finland, respectively [53] and natural and synthetic fibres were dyed with pure emodin and dermocybin found as major compounds in both Cortinarius species, as well as tap water extract. It was found that natural anthraquinones which produced light and dark colors such as yellow, orange and brown, could be suitable in dyeing and printing different textile materials.…”
Section: Resultsmentioning
confidence: 99%
“…are ectomycorrhizal fungi growing mainly in coniferous forests. Of the secondary metabolites, fungi Cortinarius, subgroup Dermocybe, are rich in monomeric anthraquinones also containing dimeric pre-anthraquinones of flavomannin type [13,[64][65][66][67][68].…”
Section: Anthraquinones In Cortinarius Semisanguineusmentioning
confidence: 99%
“…Among the more abundant compounds are emodin (13), emodin-1-glucoside, dermocybin (14), dermocybin-1-glucoside and dermorubin (15). Also, physcion (16), dermolutein, 5-chlorodermolutein, 5-chlorodermorubin, dermoglaucin, endocrocin, and erythroglaucin have been found [68]. Anthraquinones from Cortinarius species have inhibited the growth of Staphylococcus aureus and P. auerugosa [69], and many anthraquinones have bioactive properties [70].…”
Section: Anthraquinones In Cortinarius Semisanguineusmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that these dyes could be used in disperse dyeing of PET and PA without dispersing agents. A full paper entitled ‘ Fungal colorants in applications – focus on Cortinarius species ’ features in this Special Issue.…”
mentioning
confidence: 99%